(untitled) (Tanzania Medical Journal, 2023)
Background Vibrio species are reported to cause diarrhea in developing countries, particularly in Africa. The epidemiological association of Vibrio from seawater, seafood and patients’ stool and their antimicrobial susceptibility patterns has yet to be studied in Zanzibar. Therefore, this study aimed to assess epidemiological linkages of diarrheagenic Vibrio species from seawater, seafood and patient’s stools and their antimicrobial susceptibility patterns in Zanzibar, Tanzania. Methods A cross-sectional study conducted from October, 2019 to February, 2020. Twenty-seven health facilities were selected from west urban region of Zanzibar in Tanzania. Three hundred and three (303) samples of Vibrio species were randomly collected from seawater, seafood and humans for investigation. The samples were cultured using Thiosulphate - citrate - bile salts-sucrose agar and antimicrobial susceptibility (AMS) was done by Kirby–Bauer disc diffusion method. Data were analysed using Statistical Package for Social Sciences (SPSS) software (16.0 version). Descriptive statistics in frequencies and proportions were used to summarize the information collected. The multivariable analysis was used to determine the linkages of diarrheagenic Vibrio species from seawater, seafood and stool from patient with diarrhoea whereby p < 0.05 was considered statistically significant. Results Following the investigation, it was found that seawater had 60 (60.0%) of Vibrio cholerae, 57 (57.0%) were from seafood and 20(19.4%) from the patients’ stool. Similarly, 22.0% of V. parahaemolyticus were identified from seawater, 21.0% from seafood and 14.5% from patient’s stool. About 12.0% of V. vulnificus were identified from seawater,10.0% from seafood and 4.8% from patient’s stool while 6.0% of similar V. alginolyticus from seawater, 5.0% from seafood and 2.9% from patient’s stool. All Vibrio species presented sufficient susceptibility to chloramphenicol, ciprofloxacin and doxycycline with a varying pattern to trimethoprim-sulfamethoxazole. Conclusion A high proportion of diarrheagenic Vibrio species were isolated from seawater and low from patients with diarrhea. Among the tested antibiotics, three (chloramphenicol, ciprofloxacin and doxycycline) were found to be most effective for Vibrio species however. Vibrios were found to be developing resistance to four antibiotics of the commonly used antibiotics (ampicillin, erythromycin, nalidixic acid and trimethoprim-sulfamethoxazole). Interventions against diarrhoea, that address the role of Vibrio species and their corresponding antimicrobial susceptibility patterns are needed.